pH profile and acidity analysis of some Nepalese tea brands: effects of tea Type and temperature (BIBECHANA, 2024)
This study investigated the pH of four popular Nepalese tea brands such as Tokla, Ridhisidhi, Suman, and Muna, under different conditions to assess their acidity and potential health implications. The teas were prepared using standardized brewing methods, and pH measurements were taken at room temperature and after chilling to observe any temperature-related variations. Freshly brewed teas tended to be more alkaline, while those with added sugar and lemon were more acidic. Temperature changes had minimal impact on pH, indicating that acidity remains stable whether the tea is consumed hot or cold. While the pH range of these teas is generally safe for consumption, it may cause discomfort for those with acid sensitivity. These findings provide insights into the acidity of Nepalese teas and its potential effects on sensory and health attributes.